Formulating a procedure for conducting studies for evaluating the transient recovery voltage for line circuit breakers connected to evolving, series and shunt compensated transmission lines - Naidoo, Krishna (My University, 2022)
The objective of this dissertation is to develop a procedure to evaluate TRVs for Line Circuit Breakers (LCBs) connected to evolving series and shunt compensated transmission lines. The LCBs of a compensated circuit may be exposed to the effects of the change in compensation factor due to the integration of new voltage sources in this circuit which could result in higher stresses during switching. The insulation stresses related to switching the LCBs are to be evaluated in this changing environment to ensure the specified withstand requirements are adequate for the new configuration. The objective of this research is to develop an approach taking into consideration various factors that would influence the decision to uprate existing LCBs in an evolving, series and shunt compensated typical transmission network. Three scenarios were investigated in evaluating TRVs of LCBs connected to evolving series and shunt compensated transmission lines. A procedure was developed describing the approach to conducting TRV studies of LCBs connected to evolving series and shunt compensated transmission lines. Figure 1-1 presents this high-level procedure to follow. The existing network configuration must be established. This will include the fault level of the network, the fault type to apply to the simulation model (i.e. three-phase, three-phase-toground, etc.) and the phase angles of voltage sources. Next, the simulation model is to be developed by applying the appropriate component models. Input data such as transmission line tower geometry, conductors, conductor geometry, surge arrester V-I curves, series capacitor size damping circuit sizing, shunt reactor size, etc., will be required to develop an accurate model of the network being studied. Future network plans associated with the circuit being studied must be identified as this will provide input to the various scenarios to be modelled and simulated. The model should then be validated against existing fault recording data. Once the model is validated, the simulations for the various scenarios may be conducted. The results of the simulations will determine fault current limits that would result in the peak recovery voltage and RRRV ratings of the LCB being exceeded. These fault current levels will then form a trigger when these magnitudes are being reached to reassess the TRV ratings of LCBs in the circuit. This may either result in the LCB being uprated or mitigation strategies applied.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and Built Environment, School of Electrical and Information Engineering, University of Witwatersrand, Johannesburg, 2021